2020
DOI: 10.3390/ma13040943
|View full text |Cite
|
Sign up to set email alerts
|

Development of Poly(2-Methacryloyloxyethyl Phosphorylcholine)-Functionalized Hydrogels for Reducing Protein and Bacterial Adsorption

Abstract: A series of hydrogels with intrinsic antifouling properties was prepared via surface-functionalization of poly(2-hydroxyethyl methacrylate) [p(HEMA)]-based hydrogels with the biomembrane-mimicking zwitterionic polymer, poly(2-methacryloyloxyethyl phosphorylcholine) [p(MPC)]. The p(MPC)-modified hydrogels have enhanced surface wettability, high water content retention (61.0%–68.3%), and good transmittance (>90%). Notably, the presence of zwitterionic MPC moieties at the hydrogel surfaces lowered the adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 67 publications
1
23
0
2
Order By: Relevance
“…Overall, MPC demonstrated a significant antifouling effect for both proteins: for the hydrogels with the highest value of MPC, lower thickness and Δm values were obtained. This is in agreement with previous studies that found that the existence of zwitterionic MPC moieties on the surfaces of the HEMA- and silicone-based hydrogels decreased the adsorption of proteins, such as lysozyme, fibrinogen and albumin [ 56 , 57 , 58 ]. This protein repulsion capacity was attributed to the high hydration of the phosphorylcholine groups present on MPC [ 56 , 58 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, MPC demonstrated a significant antifouling effect for both proteins: for the hydrogels with the highest value of MPC, lower thickness and Δm values were obtained. This is in agreement with previous studies that found that the existence of zwitterionic MPC moieties on the surfaces of the HEMA- and silicone-based hydrogels decreased the adsorption of proteins, such as lysozyme, fibrinogen and albumin [ 56 , 57 , 58 ]. This protein repulsion capacity was attributed to the high hydration of the phosphorylcholine groups present on MPC [ 56 , 58 ].…”
Section: Resultssupporting
confidence: 93%
“…This may be due to the small amount of MPC, whose effect is minor when compared to that induced by the other hydrophilic monomers present in the hydrogel matrix. Other authors found a reduction in the water contact angle with an increase in MPC amount, but for hydrogels with MPC grafted to the surface [ 56 , 57 ] or with much higher amounts of MPC [ 58 ]. It should be noted that the contact angles obtained for all compositions fell in the range of the values typical of commercial CLs and were similar to the contact angle reported for Proclear ® (47.4 ± 7.5°) [ 59 ] using the same technique.…”
Section: Resultsmentioning
confidence: 99%
“…Contact lenses, either poly-HEMA or SiHy, surface-functionalization with poly(2-methacryloyloxyethyl phosphorylcholine) (pMPC) have enhanced surface wettability [468] and water content retention, whilst lowering the adsorption of proteins such as lysozyme and albumin and bacterial binding compared to unmodified control lenses [469,470]. The anti-biofouling properties of the pMPC-functionalised hydrogels were attributed to the dense hydration layer formed at the hydrogel surfaces by the zwitterionic coating [469,471]. The surface coating did not affect the oxygen permeability and modulus [470].…”
Section: Reducing Deposition Of Tear Film Components To Contact Lensesmentioning
confidence: 99%
“…Zwitterionic materials are a class of materials that contain both cationic and anionic groups, with no overall charge (neutral). Zwitterionic materials can be divided into the following categories according to the monomer structural characteristics (as shown in Figure 3 a): (1) phosphobetaine with a phosphate group and a terminal quaternary ammonium group [ 21 , 22 , 23 , 24 ]; (2) sulfobetaine or carboxybetaine with a quaternary ammonium group and a terminal carboxyl or sulfonic group [ 25 , 26 , 27 , 28 ]; (3) zwitterionic polyampholytes [ 29 ]. For the first two kinds of materials, each side-chain unit in the polymer contains an equal amount of positive and negative charges, which is electrically neutral.…”
Section: Structure Of Zwitterionic Materialsmentioning
confidence: 99%